Electrodeposited Cu2O Nanopetal Architecture as a Superhydrophobic and Antibacterial Surface - Subhadarshini, Suvani (Langmuir : the ACS journal of surfaces and colloids, 2019)
Bacterial infections being sporadic and uncontrollable demands an urgent paradigm shift in the development of novel antibacterial agents. This work involves the fabrication of Cu2O nanopetals over copper foil that show superlative antibacterial and superhydrophobic properties. A superhydrophobic surface has been fabricated using the electrochemical deposition (ECD) method. Here, it is aimed to establish the superior antibacterial activity as an outcome of the inherent superhydrophobic property of the as-fabricated nanostructures. The present study finds that the elevated value of the water contact angle (154 ± 0.6°) does not allow proper bacterial adhesion, and it is immune from the possibility of biofouling. Specifically, two kinds of bacterial strains have been tested and the time response of the antibacterial activity has been studied over a period of 12 h, taking DH5α Escherichia coli as a Gram-negative model and Bacillus subtilis 168 as a Gram-positive model. Higher antibacterial effects were observed for the Gram-negative model (E. coli) owing to its simplistic cell wall structure which facilitates the easy diffusion of Cu+ ions into the bacterial membrane. The simplicity of the developed method of fabrication along with the superlative superhydrophobic nature and excellent antibacterial property of the material, owing to its synergistic biophysical and biochemical modes of biocidal action, establishes its viability in many applications